Diminishing personal information privacy weakens image concerns - Riyanto, Yohanes Eko (2021)
The popularity of social media has increased users' social visibility. However, users' limited ability to control information spread could compromise privacy. People care about how others perceive them. We examined people's concerns for others' evaluations on their behaviors under different degrees of privacy conditions. Using a variant of the dictator game, we induced dictators to self-select into pro-self or pro-social types and asked recipients to give written evaluations of the dictators. We varied the degree of personal information privacy by making the written content known to the corresponding dictators only, all dictators, or either of them with equal chance. Also, the dictators could avoid receiving the message at a price. We showed that pro-self dictators' willingness to pay to conceal messages decreased when information privacy diminished. Thus, results indicated that image concerns wane in an environment where information privacy is weak. Our results contribute to understanding of the privacy paradox.